External and Internal Institutional Value Structures (Institutional Logics) in Implementing the BerAKHLAK Civil Service Core Values: Evidence from Sorong City Government, Indonesia - Atika Rafika; Hasniati Hasniati; Muh. Akmal Ibrahim; Didik Iskandar (Journal Social Civilecial, 2025)
The implementation of the BerAKHLAK civil service core values at Sorong City Government takes place within a plurality of competing institutional logics. Empirical indicators a 2023 Integrity Assessment Survey (SPI) of 58.20 (“vulnerable”), a cross-OPD synergy index of 57/100, digital system adoption below 50%, and 38% of civil servants not understanding BerAKHLAK signal that the internalisation problem is structural and rooted in a complex institutional-logics configuration. This study analyses the institutional value structure underlying BerAKHLAK implementation through the institutional logics framework , covering four dimensions: logic dominance, compatibility with BerAKHLAK values, inter-logic conflict, and balance strategies. A qualitative single-case study approach was employed. Data were collected through in-depth interviews with 34 purposively-selected informants, participant observation across seven OPDs over 48 days, and analysis of 23 official documents. Data were analysed interactively through condensation, display, and conclusion drawing, with source, method, and member-check triangulation. Bureaucratic-hierarchical and relational logics dominate practice, while BerAKHLAK logic remains subordinate and situationally active (only 8–10% in internal decisions vs 30% in externally-monitored situations). Compatibility is low-to-partial, particularly for Accountable, Competent, Adaptive, and Collaborative. Inter-logic conflict is intense (68% of implementing staff experience >3 conflicts/week) with passive resolution patterns (69% silent compromise or passive conformity). Adaptation strategies are dominated by decoupling (71% of OPDs). The dramatic 2025 surge of the Public Service Index to the Highest Green Zone (90.2) without corresponding internal improvement confirms symbolic isomorphic response over substantive value internalisation. Weak BerAKHLAK internalisation in Sorong City results from unmanaged institutional-logics configuration, where interventions stop at the symbolic level without restructuring the logic architecture that shapes bureaucratic practice. Transformation requires a paradigm shift from value socialisation to active institutional-logics management reconfiguring incentive structures, building legitimate conflict-resolution arenas, and developing systemic leadership capacity as skilled logic mediators.